Reputational risks in banks: A review of research themes, frameworks, methods, and future research directions - David Adeabah; Charles Andoh; Simplice Asongu; Albert Gemegah (African Governance and Development Institute (AGDI), 2021)
Reputation is an important factor for long-term stability, competitiveness, and success of all contemporary organizations. It is even more important for banks because of their systemic role in a modern economy. In this study, we present a review of the current body of literature regarding reputational risks in banks. Using the systematic literature review method, 35 articles published from 2010 to 2020 are reviewed and analyzed. It was found that only developed countries (i.e., the United States and Europe) have been actively contributing to research on reputational risks in banks, suggesting that reputational risks management of banks has not gained the global attention it deserves. Additionally, issues of mitigation of reputational risks are identified as the most frequently studied research theme with a paucity of research on measurement, determinants, and implications of reputational risks at both micro and macro levels. Furthermore, it was noticed that reputational risk management frameworks are still underdeveloped. In theory, this review should help with a strong conceptualization of reputational risks management in banks and guide further research.
Keywords: 330; reputational risks; banks; systematic literature review